A PLURIATIVIDADE NA AGRICULTURA FAMILIAR EM TURVO-PR - Neumann, Estevão (2016)
The pluriactivity and family agriculture are recent concepts. In Brazil began to be used more frequently from the 1990s The pluriactivity is the diversification of activities in the context of family production units, through a combination of agricultural activities with non-agricultural. We analyze the contributions and impacts pluriactivity in family agriculture of Turvo-PR, among them, check some social and economic implications brought by pluriactivity in family agriculture of Turvo; analyze the land structure of the municipality; identify agricultural and non-agricultural activities by pluriactive families, and understand the reasons / motivations for which families become pluriactive. The choice of this subject and study area justified by reason of the representativity and importance of family agriculture has for the city, for the meso-South Center of Paraná, especially, and the state of Parana. The methodological procedures of the study were based on: theoretical and conceptual framework and collection of primary data obtained in fieldwork. Found that pluriactivity in Turvo is family Agriculture is characterized by socioeconomic reproductive strategies and maintenance in rural areas.